Development of a sustainable checklist in construction - Tam, V.; Le, K.; Wang, J.; Wang, Xiangyu (2016)
Although the industry realises the importance of sustainable construction, organisations do not have enough experience and knowledge to attain sustainability. Until now, inadequate research has been carried out to support the development of sustainable culture. This paper develops a comprehensive sustainable checklist set with 67 items listed under five major phases and having three main sustainable components for use by project stakeholders. By adopting the checklist, construction organisations can continuously check missing items to successfully implement sustainability in their projects, and thus improve the overall sustainable culture. Recommendations to improve sustainability are also given: (a) establishing registrations and regulations, (b) providing guidelines, (c) establishing a governmental department, (d) providing financial support for small-size and medium-size companies and (e) providing training programmes.